The frequency of penile acne among Iraqi males with facial acne vulgaris - Salman, Husam A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Acne vulgaris is a common skin problem. It affects areas of high density of sebaceous glands like the face, chest and back. The penile skin is no exception, also can be affected with acne, however little was written on this subject. Patients & Methods: This is a clinical epidemiological study conducted at the Department of Dermatology & Venereology- Baghdad Teaching Hospital, during the period between December 2007 and May 2008. Seventy six male patients with facial acne vulgaris were enrolled in the study. A full history includes age, age of onset of facial acne and any penile lesion observed by the patient Examination of the face was done for the severity of acne and grading it into mild, moderate, severe and very severe according to Allen and Smith method. The penis of each patient was examined for the presence of ectopic sebaceous glands and acne. Results: A total number of 76 patients, their ages ranged between13 - 30 years with mean + 19.033 + 4.609. They were classified into 4 groups according to the grades of severity of acne vulgaris, 23 (30.26%), 20 (26.31%), 18 (23.68%) and 15 (19.73%) corresponding to mild, moderate, severe and very severe respectively. The frequency of ectopic sebaceous glands in these 4 groups were 15(65.21%),14(70%), 12(66.66%) and 9(60%) respectively with a total 65.78 % from all patients with facial acne. The frequency of penile acne in these 4groupswere4 (17.39%),3(15%),3(16.66%) and 2 (13.33%) with a total 15.87 % from all patients with facial acne. There was neither a statistical significant difference in the frequency of penile ectopic sebaceous glands nor of penile acne among the 4 grades of facial acne vulgaris. P value = 0.993 and 0.992 respectively. In all patients the ectopic sebaceous glands and lesions of penile acne were situated in the ventral surface of the penis. Most patients who were aware about penile lesions and afraid from having sexually transmitted disease were those having papules and pustules.Conclusion: Penile ectopic sebaceous glands were a common skin condition and penile acne was not uncommon skin problem among Iraqi males.